2020
DOI: 10.1051/epjconf/202023305011
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Global Delocalization Transition in the de Moura-Lyra Model with the Kernel Polynomial Method

Abstract: In this paper, we report numerical calculations of the localization length in a non-interacting one-dimensional tight-binding model at zero tem¬perature, holding a correlated disorder model with an algebraic power-spectrum (de Moura-Lyra model). Our calculations were based on a Kernel Polynomial implementation of the Thouless formula for the inverse localization length of a general nearest-neighbor 1D tight-binding model with open boundaries. Our results confirm the delocalization of all eigenstates in de Mour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The kernel polynomial method (KPM) [22] is a polynomial expansion-based technique and can efficiently compute the spectral function of a large disordered quantum system. It has been successfully applied to condensed matter problems [23][24][25]27], for underpinning the Anderson transitions in non-interacting disordered systems. In the KPM technique, the Hamiltonian and all energy scales need to be normalized into the standard domain of orthogonality of the Chebyshev polynomials -1 1 (] [).…”
Section: Kernel Polynomial Methodsmentioning
confidence: 99%
“…The kernel polynomial method (KPM) [22] is a polynomial expansion-based technique and can efficiently compute the spectral function of a large disordered quantum system. It has been successfully applied to condensed matter problems [23][24][25]27], for underpinning the Anderson transitions in non-interacting disordered systems. In the KPM technique, the Hamiltonian and all energy scales need to be normalized into the standard domain of orthogonality of the Chebyshev polynomials -1 1 (] [).…”
Section: Kernel Polynomial Methodsmentioning
confidence: 99%
“…With regard to the phase transition, Pires et al 41 demonstrated that the delocalization phase transition may occur at without a mobility edge in the perturbative regime. It was found that the localization length diverge as in limit in the thermodynamic limit, confirmed by the analytical perturbative calculations 41 , 42 .…”
Section: Introductionmentioning
confidence: 54%
“…The randomness in the potential is demonstrated as a long-range spatially correlated disorder under spectral density, with being the strength of correlation of the spectral density that controls the roughness of the potential landscapes. The disordered potential amplitude , is given by 39 42 , 45 , 47 , where is a normalization constant, imposing unit variance of the local potential with zero mean, and are the N /2 independent random phases which are uniformly distributed in the interval [ . It is very important to emphasize that the disorder distribution takes the following sinusoidal form of wavelength N with a vanishing noise,
Figure 1 (Color online) A schematic representation of quantum quench process under correlated Anderson model.
…”
Section: The Correlated Anderson Modelmentioning
confidence: 99%
See 2 more Smart Citations